IMPACT OF MODERNIZATION ON THE FAMILY LIFE AND SOCIAL COHESION OF AGRICULTURAL LACBORERS - Rinku Kumari (International Journal of Multidisciplinary Research and Studies, 2021)
The institution of joint families has persisted throughout India's history and is still widely practised there now. The social and economic structure of India is compatible with the joint family system, and religion has also contributed to the preservation of a joint way of life in India. In their research, Davis and Vieira Messe found that "today, dramatic changes are unfolding in the spheres of civic, social, economic, and cultural life, which are altering the paradigm of family life." These shifts are having an impact on the day-to-day activities that families engage in. As the key organizing factor of rural ties, a person's settlement is gradually taking the place of their house as the primary focus of attention. Changes in practise are being brought about by the rule of law in a substantial way. The family is an essential component of the overall operational unit of the business. The form of the gadget is undergoing a number of different revisions at the moment. As a result of a couple entering an all-blood family, the bond that unites the family is going through a period of transition. It has been said by Mrs. Ras that "The traditional Indian family is undergoing a subtle but significant social shift at the moment. Indian women who have received an education are increasingly looking for ways to express themselves outside of the context of their families since they are cut off from the traditions and attributes associated with the traditional Indian family."